Morfometrična analiza sinaptičnih jedrnih skupkov v posamičnih vlaknih hitre in počasne skeletne mišice - Smrkolj, Tomaž (Medicinski razgledi, 2001)
Myonuclei of mammalian skeletar muscle fibers are packed at much higher density in the neuromuscular junction region than in the extrajunctional partsof the fiber. Slow muscle fibers are electromechanically active for longer time periods than fast fibers and the frequency patterns of action potentials are different in both fiber types. This difference might reflect inthe distribution of synaptic myonclei and the arrangement of synaptic Schwann cells. Our hypotheses were:1. The number of synaptic myonuclei is significantly higher in slow fibers than in fast fibers. 2. The number of synaptic Schwann cells determined by counting their nuclei is proportional to the neuromuscular junction area. 3. The reach of the influences of neural trophic factors in the skeletal muscle fibers does not differ in regard to thefiber type. Nuclei in single muscle fibers of m. extensor digitorum longus (fast) and m. soleus (slow) were labelled with SYTOX green nuclear acid stain and the endplates with rhodamine-tagged alpha-bungarotoxin. Images obtained byconfocal microscopy were morphometircally analysed. There are 7,15 +- 2,37 (n=20) synaptic myonuclei in slow muscle fiber and 4,60 +- 0,75 (n = 20) synaptic myonuclei in fast muscle fiber. The difference is significantly different (p 0,05; Student's T-test).
Keywords: Muscle, skeletal; Živčnomišični stik; Anatomy and histology; Celično jedro; Hitra mišična vlakna; Neuromuscular junction; Mišica skeletna; Cell nucleus; Mišična vlakna počasna; Muscle fibers, fast-twitch; Muscle fibers, slow-twitch; Mikroskopija konfokalna; Podgane; Rats, wistar; Microscopy, confocal; skeletne mišice; anatomija; histologija; fiziologija; sinapse; molecular biology; molekularna biologija